Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.chom.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of BK Polyomaviruses from Kidney Transplant Recipients Suggests a Role for APOBEC3 in Driving In-Host Virus Evolution

Abstract: BK polyomavirus (BKV) frequently causes nephropathy (BKVN) in kidney transplant recipients (KTRs). BKV has also been implicated in the etiology of bladder and kidney cancers. We characterized BKV variants from two KTRs who developed BKVN followed by renal carcinoma. Both patients showed a swarm of BKV sequence variants encoding non-silent mutations in surface loops of the viral major capsid protein. The temporal appearance and disappearance of these mutations highlights the intra-patient evolution of BKV. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 64 publications
9
68
0
Order By: Relevance
“…ADARs interfere with viral infections directly 10 -through hypermutation of viral RNA-and indirectly, through modulation of the intracellular response (7)(8)(9)(10)(11)(12). On the other hand, APOBECs target the viral genome, typically DNA intermediates (13)(14)(15)(16)(17)(18)(19)(20), either through C-to-U hypermutation or through a non-enzymatic path that interferes with reverse transcription (21,22). Some APOBEC3 proteins can interfere in vitro with Coronaviridae replication, yet it is not clear whether their enzymatic activity is involved (23).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…ADARs interfere with viral infections directly 10 -through hypermutation of viral RNA-and indirectly, through modulation of the intracellular response (7)(8)(9)(10)(11)(12). On the other hand, APOBECs target the viral genome, typically DNA intermediates (13)(14)(15)(16)(17)(18)(19)(20), either through C-to-U hypermutation or through a non-enzymatic path that interferes with reverse transcription (21,22). Some APOBEC3 proteins can interfere in vitro with Coronaviridae replication, yet it is not clear whether their enzymatic activity is involved (23).…”
Section: Main Textmentioning
confidence: 99%
“…To assess whether RNA editing could be involved in the response to 2019-nCoV infections, we started from publicly available RNA sequencing datasets from bronchoalveolar lavage fluids (BALF) obtained from patients diagnosed with Coronavirus Virus disease (COVID-2019). While 20 transcriptomic data for all samples could be aligned to the 2019-nCoV reference genome, the quality of the sequencing varied among samples, and only two samples had coverage and error rates suitable for the identification of potentially edited sites ( Supplementary Table 1). We therefore called the single nucleotide variants (SNVs) using REDItools 2 only on the data from the two patients reported in Chen et al (27).…”
Section: Main Textmentioning
confidence: 99%
“…An important arm of the innate immune response lies in the APOBEC family of single-stranded DNA cytosine deaminases [15][16][17]. Each of the seven APOBEC3 (A3) enzymes, A3A-D and A3F-H, have been implicated in the restriction and hypermutation of a variety of different viruses including lentiviruses (HIV-1, HIV-2, HTLV-1) [18][19][20][21][22], hepadnaviruses (HBV) [23,24], endogenous retroviruses (LINE-1, Alu) [25,26], small DNA tumor viruses (HPV, JC/BK-PyV) [27][28][29][30][31], and most recently EBV [32,33]. It is difficult, if not impossible, to predict a priori which subset of APOBEC3 enzymes has the potential to engage a given virus and, furthermore, how that virus might counteract potentially restrictive A3 enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, results from the Buck lab indicated that VP1 mutations in patients with PVAN do indeed modify viral tropism and lead to neutralization escape [55]. In this study, VP1 mutations D62N, E73Q, E73K, D77H and D77N were observed in two PVAN patients with genotype IV infection, and the functional impact of these mutations was analysed using pseudotype viruses.…”
Section: Vp1 Evolution and Pathology In Jcpyv And Bkpyv Infectionmentioning
confidence: 82%